SOCIAL STUDIES TEACHER CANDIDATES SENSITIVITY AND AWARENESS LEVELS IN NATURE AND ENVIRONMENT EDUCATION - OCAL, Tulay (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2016)
As environment education gains importance in a changing and developing world, studies about this subject has been increasing every day. Nature and environment education is one of the most important subjects being studied.Environmental education applications are insufficient in the education faculties of our countrys universities. For nature andenvironmental education to reach its goals new approaches should be included in the curriculum. Many different teachingtechniques, including using field trips, can be used and new techniques can be developed.For this study, a field trip in which social studies teacher candidates had practical nature and environmental educationwas organized with 33 (20 female, 13 male) second-year teacher candidates studying Social Studies Education in NiÄŸde